Efficacy of Composite Restorative Techniques in Marginal Sealing of Extended Class V Cavities. (3rd October 2010) - Khier, Salwa; Hassan, Khamis
Abstract : Objectives . To compare the efficacy of three placement techniques in marginal sealing of Class V composite restorations extending onto the root. Materials and Methods . Class V cavities were prepared on buccal surfaces of 30 extracted human molars, with gingival margins 1.5 mm on the root. Prepared teeth were randomly assigned into 3 groups of 10 each and restored with Single Bond/Filtek Supreme using following techniques; Group I: oblique; Group II: occlusogingival; and Group III: split-increment. After restoration finishing, teeth were thermocycled, and immersed in 2% methylene blue dye for 24 h. Teeth were sectioned buccolingually. Digital photographs were made of sectioned surfaces using digital camera fitted on stereomicroscope. Microleakage was scored at occlusal and gingival margins using 0–3 scale. Dye penetration depth (DPD) at both margins was also measured using AnalySIS software. Data were analyzed using one-way ANOVA and Bonferroni multiple comparison test. Results . 5% of occlusal margins in Groups I and III had 50 μ m average (DPD). In Group II, only 10% of occlusal margins showed dye penetration, with 60 μ m average depth. For gingival margins, Groups I and III presented dye penetration in 55% of specimens, with 220 and 150 μ m average (DPD), respectively. Group II had 60% of gingival margins, with 230 μ m average (DPD). There was no significant difference in microleakage at occlusal and gingival margins in all groups. Dye penetration was larger at gingival than at occlusal margins (P < .001 ). Conclusion . None of placement techniques produced gap-free margins. Oblique and occlusogingival techniques exhibited higher degrees of microleakage at occlusal and gingival margins, as compared to that of split-increment technique. Splitting flat composite increment by diagonal cut, prior to light-curing, preserved bonded gingival margin integrity and reduced microleakage.